Factors Influencing Perception Of Health During Mandatory Work From Home (Wfh) - A Questionnaire Based Survey (Journal of Pharmaceutical Negative Results, 2023)
Background: The unprepared expeditious shift of a large number of people to WFH, requires analysis of the health problems associated with it which might enable framing guidelines on occupational health in a home office space. Thus, the study aims to find the employee’s perception of health in WFH and the factors associated with it in India.Methodology: This is a cross-sectional study of 108 participants on the perception of health among people in WFH during the COVID-19 pandemic in 2020. Convenient sampling was used and the self-designed questionnaire was administered through google forms. The study was approved by the Institutional ethical committee. Data were exported and analyzed using SPSS version 27.Results: The majority were males (73.1%) and were living in nuclear families(80.6%). About 83.4% of the participants had experienced at least one health-related problem which they would attribute to work from home(WFH). The preference for WFH was significantly lower among those who experienced health problems. The inability to maintain a work-life balance during WFH was significantly associated with health problems.Conclusion: To address the health problems, the work hours during WFH can be ensured to be within the recommended hours and maximally in the office hours. There can be legal guidelines regarding occupational health for the WFH model and soft skill training on time management skills (for work-life balance) and stress management.